Development of CRISPR-cas9 ribonucleoprotein complex platform for disruption of candidalysin in Candida albicans - Ahmad, Hasna; Ramzi, Ahmad Bazli; Arzmi, Mohd Hafiz (2020)
The ECE1 gene encodes the ECE1 protein, which is processed into the toxic peptide, candidalysin in Candida albicans. Candidalysin is responsible for host epithelial cell damage and activation of the host cell inflammasome pathway during C. albicans colonization and proliferation, and is the most recent addition to the list of virulence factors in C. albicans. CRISPR-Cas9 is being increasingly used for functional studies of virulence markers especially in animals and microbes due to its simplicity and efficiency. Previous efforts using CRISPR-Cas9 for gene editing in Candida albicans has mainly used plasmid-based approaches which require serial cloning of the Cas9 and target gRNA sequences into the plasmid before transformation into competent C. albicans cells. The process is time-consuming and is associated with off- targeting, insertional mutagenesis and poor efficiency of delivery. An alternative method for plasmid-based delivery of CRISPR-Cas9 components is delivery of a Cas9-gRNA ribonucleoprotein (RNP) complex to the cells. The Cas9-gRNA RNP complex delivery method has been described for editing in non-albicans Candida, but not in C. albicans. Here we report a Cas9-gRNA RNP complex approach instead of plasmid for disruption of the ECE1 gene and insertion of a selection marker in its locus. Three gRNAs were used to target three different locations on the ECE1 gene (upstream, middle and downstream of the gene). The gRNAs were complexed with purified Cas9 protein to generate the Cas9-sgRNA RNP complex and delivered into competent C. albicans cells via electroporation. The method is a faster, simpler and more efficient alternative to plasmid- based CRISPR-Cas9 gene editing in C. albicans.